Gas composition measurements conducted during the ABOVE field campaign at Manam volcano, Papua New Guinea, during May 2019 - Volcanic gas measurements with multi-rotor at Manam Papua, New Guinea - Galle, Bo; Arellano, Santiago (Chalmers University of Technology, 2021)
This dataset presents measurements conducted during the ABOVE (Aerial-based Observations of Volcanic Emissions) field campaign at Manam volcano, Papua New Guinea, during May 2019. The measurements were obtained with different payloads onboard a multi-rotor drone, and include data on SO2 flux, CO2 and SO2 concentration, navigation parameters, and other auxiliary information. These data are described in detailed in the article Galle et al., submitted for publication to the journal Atmospheric Measurement Techniques:

Galle, B., Arellano, S., Bobrowski, N., Conde, V., Fischer, T. P., Gerdes, G., Gutmann, A., Hoffmann, T., Itikarai, I., Krejci, T., Liu, E. J., Mulina, K., Nowicki, S., Richardson, T., Rüdiger, J., Wood, K., and Xu, J.: A multi-purpose, multi-rotor drone system for long range and high-altitude volcanic gas plume measurements, Atmos. Meas. Tech. Discuss. [preprint], https://doi.org/10.5194/amt-2020-452, in review, 2020.

Measurements conducted with a multi-rotor drone equiped with sensors for gas flux (mobileDOAS), gas composition (multiGAS and Sunkist), and several navigation and ambient sensors. Data was collected during the ABOVE field campaign at Manam volcano, Papua New Guinea.

Detta dataset presenterar mätningar utförda under fältkampanj ABOVE (Aerial-based Observations of Volcanic Emissions) vid Manam vulkanen, Papua Nya Guinea, under maj 2019. Mätningarna erhölls med olika instrument ombord på en drönare och inkluderar bland annan data om SO2-flöde, CO2 och SO2-koncentration, navigationsparametrar. Dessa data beskrivs detaljerat i artikeln Galle et al., som skickades för granskning till tidskriften Atmospheric Measuring Techniques:

Galle, B., Arellano, S., Bobrowski, N., Conde, V., Fischer, T. P., Gerdes, G., Gutmann, A., Hoffmann, T., Itikarai, I., Krejci, T., Liu, E. J., Mulina, K., Nowicki, S., Richardson, T., Rüdiger, J., Wood, K., and Xu, J.: A multi-purpose, multi-rotor drone system for long range and high-altitude volcanic gas plume measurements, Atmos. Meas. Tech. Discuss. [preprint], https://doi.org/10.5194/amt-2020-452, in review, 2020.

Mätningar utförda med en drönare utrustad med sensorer för gasflöde (mobileDOAS), gaskomposition (multiGAS och Sunkist) och flera navigations- och omgivningssensorer. Data samlades in under fältkampanjen ABOVE vid vulkanen Manam, Papua Nya Guinea.
Gasmätningar utförda under fältkampanj ABOVE vid Manam vulkanen, Papua Nya Guinea, under maj 2019 - Vulkaniska gasmätningar med drönare på Manam Papua, Nya Guinea
Keywords: ATMOSPHERE; meteorology; meteorologi; Atmospheric conditions; Atmosfäriska förhållanden; drone; drönare; Manam volcano; Vulkan Manam; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Geoscientific Information; Geovetenskap